Przydatność polskich danych internetowych w prognozowaniu - Gondek, Anna (Usefulness of Polish Internet Data in Forecasting Area, 2006)
This article presents research about usefulness of Polish Internet data in forecasting for enterprise. There are six stages of research presented in the article. The criterion of opinion about Internet sides was data quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 207-218